Virtuous Minds : Intellectual Character Development. - Dow, Philip E. (InterVarsity Press, 2013)
Teacher-administrator Philip Dow explores the implications of setting intellectual character (rather than intellectual content) at the heart of our educational programs. With ample stories and practical suggestions, Dow shows how intellectual virtues like tenacity, carefulness and curiosity are teachable traits that can produce good lives.